2015
DOI: 10.1097/rlu.0000000000000772
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Coregistration Accuracy of Pelvic Structures Between Sequential and Simultaneous Imaging During Hybrid PET/MRI in Patients with Bladder Cancer

Abstract: Purpose The aim of this study was to compare coregistration of the bladder wall, bladder masses, and pelvic lymph nodes between sequential and simultaneous PET and MRI acquisitions obtained during hybrid 18F-FDG PET/MRI performed using a diuresis protocol in bladder cancer patients. Methods Six bladder cancer patients underwent 18F-FDG hybrid PET/MRI, including IV Lasix administration and oral hydration, before imaging to achieve bladder clearance. Axial T2-weighted imaging (T2WI) was obtained approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 28 publications
0
17
0
2
Order By: Relevance
“…An additional study of fluorocholine PET/MRI in patients awaiting radical prostatectomy observed excellent correlation between abnormalities on T2-weighted images and areas of increased uptake and higher accuracy for tumor using PET/MRI compared with MRI alone [64]. We have shown the ability to evaluate prostate cancer using graphic analysis with an image-derived arterial input function based on dynamically acquired PET data obtained immediately after nearly simultaneous injection of both PET and MRI contrast agents as part of a hybrid PET/MRI examination [65]. Our data suggested added potential of the dynamic PET metrics compared with traditional static PET metrics, such as SUV obtained at a delayed equilibrium time point after radiotracer injection.…”
Section: Clinical Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional study of fluorocholine PET/MRI in patients awaiting radical prostatectomy observed excellent correlation between abnormalities on T2-weighted images and areas of increased uptake and higher accuracy for tumor using PET/MRI compared with MRI alone [64]. We have shown the ability to evaluate prostate cancer using graphic analysis with an image-derived arterial input function based on dynamically acquired PET data obtained immediately after nearly simultaneous injection of both PET and MRI contrast agents as part of a hybrid PET/MRI examination [65]. Our data suggested added potential of the dynamic PET metrics compared with traditional static PET metrics, such as SUV obtained at a delayed equilibrium time point after radiotracer injection.…”
Section: Clinical Examplesmentioning
confidence: 99%
“…6). Preliminary data indicate that simultaneous PET and MRI acquisitions from hybrid PET/MRI achieve substantially improved coregistration of the bladder wall and slightly improved coregistration of bladder masses and pelvic lymph nodes compared with sequential acquisitions [65]. This PET/MRI protocol is being investigated for purposes such as identification of recurrent bladder tumor after transurethral tumor resection as well as prediction and monitoring of response to neoadjuvant chemotherapy.…”
Section: Clinical Examplesmentioning
confidence: 99%
“…Benzer biçimde jinekolojik kanserlerde entegre FDG PET/MR görüntüleme lokal tümör yayılımının ve lenf nodu tutulumunun belirlenmesi için kullanışlı bir yöntemdir. MR'ın yüksek yumuşak doku rezolüsyonu ve fonksiyonel görüntüleme özellikleri overlerin, uterusun, prostatın ve mesanenin primer tümör özelliklerinin belirlenmesine ve peritoneal yayılımın araştırılmasına katkıda bulunur (27). Prostat kanserinin tanısında morfolojik (T2 ağırlıklı) ve fonksiyonel (difüzyon ağırlıklı, kontrastlı) multi-parametrik MR görüntülerinden yararlanılır (28).…”
Section: Pelvisbölgesiunclassified
“…Entegre PET/MR sistemlerinde metabolik ve anatomik bilginin daha iyi registrasyonu, mesane duvarının, lezyonların ve pelvik lenf nodlarının değerlendirilmesinde yarar sağlamaktadır (124). Tüm vücut PET/MR görüntüleme, mesane kanserlerinde primer mesane tümörlerinin değerlendirilmesinin yanı sıra, aynı görüntüleme seansı içerisinde kemik ve yumuşak doku uzak metastaz varlığının araştırılmasında da sağladığı kombine metabolik-fonksiyonel-anatomik verilerle etkili olma potansiyeli taşımaktadır.…”
Section: Mesanekanserindepet/mrunclassified